Buite-aardse rasionaliteit: Uitvlug in fantasie of grootste uitdaging ooit aan filosofie en teologie? - Antonites, A. J. (Hervormde teologiese studies, 1996)
Extra terrestrial intelligence: Escape in fantasy or greatest challenge to philosophy and theology ever? The concept of extra-terrestrial intelligence was first mooted by philosophers like Aristotle and Lucretius as well as natural scientists like Huygens and Whewell. It is considered whether UFO reports rather than indicating something real provide a symptom of the current religious cultural situation in Europe. Should rational life elsewhere in the universe be real, it is argued that biological life would be a neccessary condition. The divergence and convergence hypotheses are examined.The fundamental prerequisite is the existence of other solar systems with planets other than our own. Insights from biology and astronomy are placed in the context of philosophical discourse.